PROTOTYPE PENGECEKAN SUHU TUBUH UNTUK MENCEGAH COVID-10 BERBASIS INTERNET OF THINGS DI UNIVERSITAS PGRI KANJURUHAN MALANG - Maharani, Delvi Anjarita; Nugraha, Danang Aditya; Aziz, Abdul (Institut Teknologi Nasional Malang, 2023)
The world of health is in an uproar with the discovery of a new type of virus, namely Corona Virus-2 (SARS-CoV-2) and the name of the disease as Corona virus disease 2019 (COVID-19). This virus is easily spread contagious. Therefore, to prevent transmission of this virus, the government makes regulations for the community to minimize physical contact with the outside world and avoid crowds, which is also known as physical distancing , namely limiting the distance between people from one another. The impact of this virus has caused many community activities to be disrupted, including the process of teaching and learning activities so that several institutions carry out online. One of the symptoms suffered by people exposed to COVID-19 is a high body temperature at > 37.5°C so it is necessary to carry out periodic checks without touching (non-contact). With these problems, a prototype for checking body temperature based on the Internet of Things was made. The way the Internet of Things is by creating or embedding arguments in programming form. Argument commands create interactions between remotely connected machines when connected to the Internet. In this study, the design of a body temperature checking device uses an MLX90614 sensor with an Arduino Uno microcontroller, 12c LCD as display output. The results of testing the design of this system, the resulting MLX90614 sensor reading accuracy test was obtained at 99.6%. This indicates that the MLX90614 sensor is functioning properly.